Sodium and acidic alginate foams with hierarchical porosity: Preparation, characterization and efficiency as a dye adsorbent. (15th December 2017) - Pettignano, Asja; Tanchoux, Nathalie; Cacciaguerra, Thomas; Vincent, Thierry; Bernardi, Luca; Guibal, Eric; Quignard, Françoise
Graphical abstract: Highlights: Sodium alginate foams by ice-templating followed by freeze-drying. Formulation and processing parameters determine the structure of the foams. Preparation of acidified macro/meso-porous foams with high surface area. Alginic acid foam is a competitive sorbent for a cationic dye, methylene blue. Abstract: A novel approach for the preparation of sodium alginate foams by ice-templating, followed by freeze-drying was described. Important effects of the preparation parameters on the macroporous structure of the final materials could be evidenced. A functionalization procedure for the preparation of acidified macro/meso-porous foams with high surface area was optimized and the efficiency of one alginic acid foam was demonstrated for the adsorption of a basic dye (methylene blue) from aqueous solution. The comparison of the maximum monolayer adsorption capacity of this adsorbent with the values already reported for other biosorbents clearly identified alginic acid foams as competitive sorbents for the removal of methylene blue from aqueous solutions.